Massive pericardial effusion after Nuss procedure: to drain or not to drain? - Yu, Peter S. Y.; Ng, Vikki W. K.; Lau, Rainbow W. H.; Ng, Calvin S. H. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
A 11-year-old boy presented with refractory fever and dyspnoea after Nuss procedure. Massive pericardial effusion was detected on computer tomography scan performed under corticosteroid cover for his asthmatic history. With rapid clinical improvement following corticosteroids, a clinical diagnosis of post-pericardiotomy syndrome (PPS) was made. Following a course of oral prednisolone, serial blood test and echocardiogram showed gradual resolution of inflammation and pericardial effusion. This rarely-reported case serves as a poignant reminder to PPS after Nuss procedure as a cause of febrile massive pericardial effusion. Early therapeutic trial of corticosteroids may prevent clinical deterioration, and have invasive pericardial drainage avoided.